Kemampuan Basic Knolwledge Guru Sekolah Dasar Peserta Program Pendidikan Profesi Guru - Rizki Putri Wardani; Chumi Zahroul Fitriyah (Jurnal Penelitian Pendidikan, 2022)
The Teacher Certification Program was an educational form that aimed at increasingthe professionalism of teachers. The aim of this research was to describe before and after basic knowledge of primary teachers that has been already joining in Teacher Certification Program. Basic knowledge is knowledge about understanding lesson plans which is suitable with basic competence, lesson theory, until research plan after teaching to support teacher professionalism. The research method was a quantitative description. Technique this research was an interview with a primary teacher that has been already joining the teacher certification program. Data analysis using a percentage of basic knowledge before and after primary teacher. Data result has been shown basic knowledge primary teacher is increased from arranging lesson plan for doing research and reflection in the learning process Pendidikan Profesional Guru merupakan bentuk pendidikan yang ditujukan bagi guru untuk meningkatkan keprofesionalan guru. Tujuan dari penelitian ini untuk mendeskripsikan kemampuan dasar atau Basic Knowledge guru Sekolah Dasar sebelum dan sesudah mengikuti Pendidikan Profesional Guru (PPG). Kemampuan dasar atau basic knowledge merupakan kemampuan yang meliputi pemahaman rencana pembelajaran yang sesuai kompetensi dasar, pemahaman teori belajar, hingga penelitian setelah pembelajaran untuk mendukung profesional guru. Metode dalam penelitian ini adalah deskriptif kuantitatif. Teknik wawancara dilakukan dalam penelitian ini dengan subjek guru sekolah dasar yang telah megikuti PPG. Analisis data menggunakan hasil presentasi kemampuan guru sebelum dan sesudah mengikuti PPG. Hasil penelitian menunjukkan bahwa kemampuan Basic Knowledge guru Sekolah Dasar meningkat, dimulai dari kemampuan melakukan perencanaan sampai melakukan penelitian perbaikan dalam pembelajaran.